1997
DOI: 10.1289/ehp.97105598
|View full text |Cite
|
Sign up to set email alerts
|

Geographic information systems: their use in environmental epidemiologic research.

Abstract: Advances in geographic information system (GIS) technology, developed by geographers, provide new opportunities for environmental epidemiologists to study associations between environmental exposures and the spatial distribution of disease. A GIS is a powerful computer mapping and analysis technology capable of integrating large quantities of geographic (spatial) data as well as linking geographic with nongeographic data (e.g., demographic information, environmental exposure levels). In this paper we provide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(46 citation statements)
references
References 11 publications
1
43
0
1
Order By: Relevance
“…The attribute data within the tax parcel dataset were used to geocode blood lead surveillance data, as well as to determine the year built for houses where screened children resided. Potable service districts data were downloaded from the Wayne County GIS spatial data explorer (Wayne County GIS Department 2006). This dataset contains basic data for each of the water systems within Wayne County, including district name, number, and land area.…”
Section: Methodsmentioning
confidence: 99%
“…The attribute data within the tax parcel dataset were used to geocode blood lead surveillance data, as well as to determine the year built for houses where screened children resided. Potable service districts data were downloaded from the Wayne County GIS spatial data explorer (Wayne County GIS Department 2006). This dataset contains basic data for each of the water systems within Wayne County, including district name, number, and land area.…”
Section: Methodsmentioning
confidence: 99%
“…Several publications describe the structure and functionality of a GIS more thoroughly (Chrisman 2002; DeMers 2000). Vine et al (1997) provide an overview of the use of specific functions in GIS software that could be useful in environmental epidemiologic research. Beyea and Hatch (1999) provide an in-depth discussion of geographic modeling for exposure assessment in environmental epidemiology, as well as an extensive literature review.…”
mentioning
confidence: 99%
“…The study also found that geocoding status was independently associated with air pollution exposures. In addition, rural addresses are more difficult to locate due to the use of rural roads and post office boxes (15, 29). This pattern is consistent with our study which found that the majority of ungeocoded addresses were in rural areas.…”
Section: Discussionmentioning
confidence: 99%